Geomechanical Analysis to Avoid Serious Drilling Hazards in Zubair Oilfield, Southern Iraq - Shaban, Shaban Dharb; Hadi, Hassan Abdul (Iraqi Journal of Science, 2020)
Zubair oilfield is an efficient contributor to the total Iraqi produced hydrocarbon. Drilling vertical wells as well as deviated and horizontal wells have been experiencing intractable challenges. Investigation of well data showed that the wellbore instability issues were the major challenges to drill in Zubair oilfield. These experienced borehole instability problems are attributed to the increase in the nonproductive time (NPT). This study can assist in managing an investment-drilling plan with less nonproductive time and more efficient well designing. To achieve the study objectives, a one dimension geomechanical model (1D MEM) was constructed based on open hole log measurements, including Gamma-ray (GR), Caliper (CALI), Density (RHOZ), sonic compression (DTCO) and shear (DTSM) wave velocities , and Micro imager log (FMI). The determined 1D MEM components, i.e., pore pressure, rock mechanical properties, in-situ principal stress magnitudes and orientations, were calibrated using the data acquired from repeated formation test (RFT), hydraulic fracturing test (Mini-frac), and laboratory rock core mechanical test (triaxial test). Then, a validation model coupled with three failure criteria, i.e., Mohr-Coulomb, Mogi-Coulomb, and Modified lade, was conducted using the Caliper and Micro-imager logs. Finally, sensitivity and forecasting stability analyses were implemented to predict the most stable wellbore trajectory concerning the safe mud window for the planned wells. The implemented wellbore instability analysis utilizing Mogi-Coulomb criterion demonstrated that the azimuth of 140o paralleling to the minimum horizontal stress is preferable to orient deviated and horizontal wells. The vertical and slightly deviated boreholes (1ess than 30o) are the most stable wellbores, and they are recommended to be drilled with 11.6 -12 ppg mud weight. The highly deviated and horizontal wells are recommended to be drilled with a mud weight of 12-12.6 ppg.